The Soft X-Ray Aspect of Gamma-Ray Bursts in the Einstein Probe Era - Hao-Xuan Gao; Jin-Jun Geng; Yi-Fang Liang; Hui Sun; Fan Xu; Xue-Feng Wu; Yong-Feng Huang; Zi-Gao Dai; Wei-Min Yuan (The Astrophysical Journal)
The Einstein Probe (EP) satellite, dedicated to time-domain high-energy astrophysics and multimessenger astronomy, was recently launched and successfully put into operation. The Wide-field X-ray Telescope (WXT; 0.5–4 keV) on board has identified multiple gamma-ray burst (GRB) events, with an average duration of several hundred seconds. This duration is several times longer than the average duration of long gamma-ray bursts (LGRBs) detected by the Neil Gehrels Swift Observatory, which typically stands at several tens of seconds. Additionally, EP has detected some unknown X-ray transients whose connection to GRBs is uncertain, due to the absence of gamma-ray counterparts and efficient follow-up observation at multiple wavelengths. Several main factors could account for the longer time, including the Doppler effect of off-axis viewing, the spectral lag effect of the synchrotron spectrum of cooling electrons, and some unknown prolonged intrinsic X-ray activities. Our studies indicate that EP GRBs may primarily consist of off-axis-viewed bursts, forming a unique population among the GRB zoo, yet the intrinsic origin for the specific bursts could not be excluded. By analyzing the statistical properties of the historical LGRB samples, we explored observable properties of on-axis and off-axis LGRBs in the soft X-ray band. The predicted characteristics of off-axis-viewed GRBs, including the duration, the energy fluence, the low-energy spectral index, and the slopes of the Amati and Yonetoku relations, could be tested with a larger sample of GRB events detected by EP in the future.